Digital Workflow for Fixed Implant Rehabilitation of an Extremely Atrophic Edentulous Mandible in Three Appointments. Issue 3 (18th March 2017) - Papaspyridakos, Panos; Rajput, Neha; Kudara, Yukio; Weber, Hans‐Peter
Abstract: Objective: To present a rationale to reduce treatment complexity, number of surgeries, and overall treatment time for patients with extreme mandibular ridge deficiency. Clinical Considerations: A 67‐year‐old fully edentulous male presented with a chief complaint of poor retention and stability of the mandibular complete denture with consequent discomfort and inability to chew. A novel 3‐appointment protocol from guided implant placement to definitive prosthesis delivery was implemented. At the first appointment, a guided surgery protocol with the All‐on‐4 concept was used in the mandible. Implant placement was followed by immediate loading with a fixed provisional prosthesis providing the patient with immediate function. Final impression, cast verification and articulation, determination of VDO, and interocclusal records were obtained in the same appointment. In the second appointment, the framework try‐in was performed and a pick‐up impression was taken after a new CR record. The third appointment included the delivery of the final screw‐retained, one‐piece, full‐arch prosthesis opposed by a maxillary complete denture. Conclusion: This expedited protocol allows for implant placement with a surgical template generated from preoperative virtual planning of the implants and the CAD/CAM prosthodontic rehabilitation using a digital workflow. The patient was satisfied with the esthetic and functional outcome and was enrolled into a 6‐month recall program. Clinical Significance: This article describes an expedited protocol illustrating a digital workflow for full arch implant rehabilitation of the extremely atrophic mandible. Flapless implant placement with a surgical template generated from virtual planning was followed by immediate loading with a fixed prosthesis. Digital impression/digitization of the working cast and CAD/CAM technology were used to mill the definitive prosthesis. From guided surgery to the definitive rehabilitation only three appointments were necessary. This digital workflow can enhance patient acceptance and comfort and serve as an alternative treatment in the indicated clinical scenario. (J Esthet Restor Dent 29:178–188, 2017)